Human Trafficking and Sex Slaves: How is International Law Enforcement in the Southeast Asian Region? - Luqmanulhakim, Naufal; Latifah, Emmy (Journal of ASEAN Dynamics and Beyond, 2022)
Human trafficking and sex slaves are global problems that are very threatening. Southeast Asia is one of the centers of human trafficking activities causing a sense of insecurity in society. This research entitled Human Trafficking and Sex Slaves: How is International Law Enforcement in the Southeast Asian Region seeks to examine how ASEAN and its member countries make and apply international law to eradicate human trafficking. The data collection method used is descriptive qualitative. The results of the research show that there have been many efforts by ASEAN and its member countries against human trafficking. The established conventions and policies are a big boost for the ASEAN community to be aware of and participate in the fight against human trafficking. However, the efforts made by ASEAN are considered less effective due to the unique and distinctive structure of ASEAN society. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//